Analysis of Indonesia’s Rising Economic Protectionism since Yudhoyono’s Era - Herdianto, Enggar Furi (Papua Journal of Diplomacy and International Relations, 2023)
Protectionism is not a new economic policy for Indonesia. This policy has been taken since Sukarno’s era. Even though the liberal approach was rising after the 1997 crisis, the return to protectionist policy was still visible in the Susilo Bambang Yudhoyono’s era, and further advanced by Joko Widodo. This article focuses on analysing the rising protectionist policy in Indonesia’s economy since the Yudhoyono era. It employs a qualitative approach by utilizing related secondary data. It shows that the Indonesian protectionism taken by the government was influenced by domestic, regional, and global conditions. This protective measure was taken to make sure that the domestic industry could cover the demand in the domestic market within a more liberalized global market. In doing this, various approaches have been developed including, incentives for domestic companies and declaring content requirements for the products sold in the domestic market. This research will help to understand better on the nature of Indonesia’s economic policy, mapping economic opportunities that could be maximized by the government, and how it then affects international economic actors’ strategy on entering the market. KEYWORDS Domestic Market; Economy; Protectionism